A systematic review of digital technology-enhanced strategies in music education: Implications for South African higher education learning - Sakhiseni Joseph Yende (CV. Yudhistt Fateeh, 2026)
This article contributes to scholarship on music education and digital pedagogy by providing a systematic synthesis of digital and technology-enhanced teaching strategies in higher education music learning, with a specific focus on the South African context. While existing studies have explored the benefits and limitations of digital learning, this review offers new insights by consolidating fragmented research on technology-mediated music pedagogy and examining how these approaches function within the socio-economic and educational realities of South African universities. By applying PRISMA-guided systematic review methods to literature published between 2015 and 2025, the study identifies emerging pedagogical patterns and highlights the ways in which digital tools reshape both theoretical instruction and practical musicianship in tertiary music education. The originality of this study lies in its contextual emphasis on digital inequality and culturally responsive pedagogy in music education. The review demonstrates how digital platforms such as virtual rehearsal environments, collaborative online spaces, and digital archiving tools can support multilingual engagement and the preservation and dissemination of indigenous musical knowledge. In doing so, the study extends current debates in digital pedagogy by foregrounding the role of technology in sustaining culturally relevant music education practices. Furthermore, the article advances scholarship by linking technological innovation in music education to broader structural challenges in South African higher education. It highlights how disparities in digital infrastructure, institutional resources, and digital literacy shape the implementation of technology-enhanced learning. These findings inform curriculum reform and national policy debates on equitable digital transformation in South African higher education music programmes nationwide.